THE INSTITUTIONAL ENVIRONMENT FOR THE FUNCTIONING OF THE FISCAL MECHANISM FOR REGULATING INVESTMENT PROCESSES - Melnik, V.M.; Rudenko, V.V. (The actual problems of regional economy development, 2020)
Modern processes of fiscal policy development and implementation have brought up the issues of forming the institutional environment of the fiscal mechanism for regulating investment processes, because at the institutional level norms, values, stereotypes, ideas, behavior are formed and modified, the change of which leads to global consequences. The functioning of institutions explains the situation in which, with equivalent processes in the economic systems of different countries with the use of universal technologies of reforming and modernizing the economy, fundamentally different results of innovations are recorded. That is, the effectiveness of fiscal policy depends crucially on the institutions that regulate the life of society as a whole. And whatever the views of scientists were on the nature and conditions of institutions’ occurrence, it must be recognized that they have an undeniable influence on the fiscal mechanism for regulating the investment processes. The article is devoted to the study of topical issues of building an institutional environment for the functioning of the fiscal mechanism for regulating investment processes. The specifics of scientific tasks being the subject of the research required the use of a complex of methods which enabled to determine the content and components of the institutional environment of the fiscal mechanism for regulating investment processes. In the article the formation and development of institutional theory are investigated, as well as the essence of the concept of “institution” is defined. The essence and components of the institutional environment of functioning of the fiscal mechanism of regulation of investment processes are considered. The functions and characteristic properties of the institutional environment of functioning of the fiscal mechanism of regulation of investment processes are determined. As a result of the research it is proved that the institutional environment of functioning of the fiscal mechanism of regulation of investment processes creates restrictive social borders for making individual decisions, sets the system of positive and negative incentives, directing the activity of individuals in a certain direction. The main components of this environment are an orderly set of formal and informal rules and organizations (institutions) that perform certain functions, have a fiscal impact on the investment sphere and generate transaction-sensitive transaction costs.